Microstructural evolution and mechanical properties of thixoformed A319 alloys containing variable amounts of magnesium - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Alhawari, Khalid Salim; Mohammed, Mohammed Naser; Md Ali, Mohd Amran; Mohamad, Effendi (Elsevier, 2016)
The effects of Mg content on the microstructure and tensile properties of thixoformed A319 alloys were studied. The samples were thixoformed at 50% liquid content and some of the thixoformed samples were subjected to the T6 heat treatment. The samples were then examined by optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy and X-ray diffraction (XRD) analysis as well as tensile tests. The results showed that magnesium was able to refine the eutectic silicon in the samples. It was also observed that a compact Al9FeMg3Si5 phase was formed when the magnesium content was 1.0% and 1.5%. The results also revealed that as the magnesium content in the alloy increases, the tensile strengths of the thixoformed alloys also increase. The ultimate tensile strength, yield strength and elongation to fracture of the thixoformed A319 heat treated alloy were 298 MPa, 201 MPa and 4.5%, respectively, whereas the values of the thixoformed heat treated alloy with 1.5% Mg content were 325 MPa, 251 MPa and 1.4%, respectively. Thixoformed A319 alloy showed a dimple fracture behaviour, while thixoformed A319 alloys with 1.5% Mg showed a mixed mode fracture behaviour, where dimple and cleavage ruptures were seen on the fracture surface of the samples.